2014
DOI: 10.1021/jm401316v
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Determinants of Trace Amine-Associated Receptor 1’s Functional Selectivity for the Stereoisomers of Amphetamine and Methamphetamine

Abstract: Amphetamines are widely abused drugs that interfere with dopamine transport and storage. Recently, however, another mechanism of action was identified: stereoselective activation of the GαS protein-coupled trace amine-associated receptor 1 (TAAR1). To identify structural determinants of this stereoselectivity, we functionally evaluated six mutant receptors in vitro and then used homology modeling and dynamic simulation to predict drug affinities. Converting Asp102 to Ala rendered mouse and rat TAAR1 (mTAAR1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…Instead, heightened sensitivity to MA-induced hypothermia was associated with low MA intake and greater sensitivity to MA-induced aversion. MA is an agonist at TAAR1 (Bunzow et al, 2001;Reese et al, 2014;Wolinsky et al, 2007) and the outcome of hypothermia is in agreement with other reports of TAAR1 agonist-induced hypothermia in rodents (Di Cara et al, 2011;Fantegrossi et al, 2013;Panas et al, 2010;Sabol et al, 2013). Thus, it appears that TAAR1 mediates MA-induced hypothermia and that the immediate hypothermic effect of MA may have a role in curbing MA intake in MALDR, Taar1 +/+ and Taar1 +/ − mice.…”
Section: Taar1 and Methamphetamine Intakesupporting
confidence: 91%
“…Instead, heightened sensitivity to MA-induced hypothermia was associated with low MA intake and greater sensitivity to MA-induced aversion. MA is an agonist at TAAR1 (Bunzow et al, 2001;Reese et al, 2014;Wolinsky et al, 2007) and the outcome of hypothermia is in agreement with other reports of TAAR1 agonist-induced hypothermia in rodents (Di Cara et al, 2011;Fantegrossi et al, 2013;Panas et al, 2010;Sabol et al, 2013). Thus, it appears that TAAR1 mediates MA-induced hypothermia and that the immediate hypothermic effect of MA may have a role in curbing MA intake in MALDR, Taar1 +/+ and Taar1 +/ − mice.…”
Section: Taar1 and Methamphetamine Intakesupporting
confidence: 91%
“…Species differences in TAAR1/ligand interactions have been predicted from sequence alignment studies that compared the critical residues for the binding of b-PEA, showing that amino acids that correspond to the critical residues differ between rat, mouse, and human TAAR1 (Kratochwil et al, 2011). Sitedirected mutagenesis studies have identified two locations in TAAR1 transmembrane domains 6 and 7, where amino acid substitutions markedly reduce or increase methamphetamine TAAR1 activation potencies in the rat and mouse TAAR1 (Reese et al, 2014). Docking studies with a homology model for the human TAAR1 (Cichero et al, 2013(Cichero et al, , 2014 could serve to further elucidate the essential amino acids that are required for ligand binding and discover structural determinants for the TAAR1 activity or inactivity of psychoactive substances.…”
Section: Discussionmentioning
confidence: 99%
“…TAAR1 is stimulated by endogenous ligands, including b-phenylethylamine (b-PEA), p-tyramine, tryptamine, and 3-iodothyronamine (Scanlan et al, 2004;Zucchi et al, 2006). Many psychoactive compounds, including amphetamine and phenethylamine derivatives, also bind to TAAR1 (Bunzow et al, 2001;Wainscott et al, 2007;Simmler et al, 2013;Reese et al, 2014). The activation of TAAR1 results in elevations in intracellular cAMP (Bunzow et al, 2001;Xie and Miller, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has become clear that, aside from these traditional mechanisms, amphetamines are also capable of modulating action potential-dependent neurotransmitter release (Branch and Beckstead, 2012;Daberkow et al, 2013). Furthermore, amphetamines regulate DA neurotransmission via inhibition of monoamine oxidase (MAO) and enhancement of tyrosine hydroxylase (TH) and have numerous other receptor targets, including the a2-adrenergic receptor, the sigma receptor, and the trace amine-associated receptor 1 (TA 1 ) receptor (Fung and Uretsky, 1982;Robinson, 1985;Ritz and Kuhar, 1989;Matsumoto et al, 2014;Reese et al, 2014). Many of these targets have been identified only recently, and their importance in mediating the effects of amphetamines on behavior as well as its therapeutic, reinforcing, and toxic effects are just beginning to be understood.…”
Section: B Amphetamine-type Psychostimulantsmentioning
confidence: 99%